IMPLEMENTATION OF ISLAMIC SOCIAL REPORTING IN ISLAMIC BANKS MALAYSIA - Yuniorita Indah Handayani (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2017)
The objectives of this study are (1) to measure the extent to which the Islamic Social Reporting (ISR) is practiced by Islamic banks in Malaysia and (2) to examine the ISR aspect which is most widely disclosed in annual reports. This study used ten Islamic banks in Malaysia as the research sample. The data used were secondary data in the form of information about social activities reported in 2015, 2016, and 2017. The analytical method used was content analysis technique and scoring to assess social activities disclosed in annual reports of the research object. The results showed that the average level of disclosure of the ISR of Malaysian Islamic banks was 32.81%, while the theme that had the highest level of disclosure was society with 10.77%.